Grupo TAPA: An Overview of The Work of a Brazilian Repertory Theater Company - Betti, Maria Sílvia (ABEI Journal, 2023)
This article contextualizes and briefly discusses the most important characteristics of Grupo TAPA’s work and acting methods. Special emphasis is given to the formative process in the area of acting and to the involvement of the group with the translation of plays by particularly relevant playwrights like Tchecov and Tennessee Williams.